The spatial ecology of Albula glossodonta in the St. Joseph Atoll, Seychelles - Moxham, Emily Jeanne (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2018)
Bonefish (Albula spp.) support valuable recreational and artisanal fisheries worldwide. Declining stocks have been reported at multiple localities, potentially jeopardising numerous multimillion-dollar industries. In particular, tourism generated through bonefish fly fishing contributes considerably to the economies of many isolated tropical islands and atolls. However, despite their economic value, little is known about bonefish in the Indian Ocean. This study aimed to contribute to the understanding of bonefish ecology in the Indian Ocean by (1) reviewing the bonefish literature to identify knowledge gaps; (2) evaluating the postrelease survival of acoustically tagged bonefish and; (3) quantifying the spatial and temporal movements of bonefish at a near-pristine and predator rich atoll in the Seychelles. A review of published literature on bonefish indicated that despite considerable biological and ecological research in the Pacific and Atlantic oceans, virtually no research has been conducted in the Indian Ocean. To help address this research gap, an acoustic telemetry study was initiated at the remote St. Joseph Atoll, within an existing array of 88 automated datalogging acoustic receivers. Thirty Albula glossodonta were surgically implanted with Vemco V13 acoustic transmitters in May 2015 and tracked for a period of one year. Only 10% of the tagged bonefish were detected for more than two weeks. A comparison of the final 100 hours of movement data from fish that were detected for less than two weeks to fish detected for longer periods revealed distinct differences. These included differences in area use patterns and significant differences in the average daily distance moved, speed of movement and residency index. This suggested that mortality in the form of post-release predation was high (90%) with tagged fish detected for less than two weeks being preyed upon by sharks. The three surviving bonefish were tracked for 210 to 367 days. These individuals remained in the atoll and showed high use of the marginal habitats between the shallow sand flats and the deeper lagoon. Water temperature, diel cycle and tide were significant predictors of bonefish presence in the lagoon. The high post-release predation of bonefish has implications for the management of this and other Albula species. Despite these fisheries being catch-and-release, bonefish fishing may be unsustainable due to the high post-release mortality, particularly in areas that are rich in predators. Therefore, protected areas or limitations on fishing effort need to be considered.
Keywords: Bonefish -- Seychelles -- Amirante Islands; Albula -- Seychelles -- Amirante Islands; Bonefish fisheries -- Seychelles -- Amirante Islands; Small-scale fisheries -- Seychelles -- Amirante Islands -- Economic conditions; Underwater acoustic telemetry; Bonefish -- Behavior -- Seychelles -- Amirante Islands; Bonefish -- Home range -- Seychelles -- Amirante Islands; Bonefish -- Conservation -- Seychelles -- Amirante Islands; Predation (Biology) -- Seychelles -- Amirante Islands; Bonefishing